IDENTIFIKASI MASALAH KEKUMUHAN KAMPUNG TEPIAN SUNGAI STUDI KASUS KELURAHAN BANSIR LAUT, SUNGAI KAPUAS, KOTA PONTIANAK - Bianca, Yovi; Herlambang, Suryono; Suryadjaja, Regina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
Development in Pontianak City tends to focus on land areas  neglecting riverside communities in terms of proper water resource management. The living conditions in these communities, particularly those along the Kapuas River banks, are concerning. These villages are considered uninhabitable due to the emergence of slum organizational problems such as building irregularities, high levels of building density, the quality of building structures, environmental facilities and infrastructure that do not meet technical requirements and do not serve the organization, as well as public facilities and social facilities that do not affordable for its residents. One of them is Caping Village and Tudong Village. Even though there have been efforts to organize slum areas that have been realized by government programs, apart from the image of the organization area on the banks of the river in Kampung Caping and Kampung Tudong which has not been able to provide beauty and sustainable greening to its physical environment, the organization area also does not have the capability to providing the need for environmental infrastructure to support the activities of people living in villages on the banks of the Kapuas River. Therefore, this research was carried out with the hope of identifying the existing slum problems that occur in Kampung Caping and Kampung Tudong. This research will be carried out using descriptive methods, analysis of existing conditions, and analysis of regulatory standards in accordance with the provisions of ministerial regulations and national standards. Keywords: kapuas river; riverside; slum area Abstrak Orientasi kehidupan dan permukiman masyarakat kota Pontianak cenderung berkembang di daerah daratan sehingga permukiman yang ada pada tepian dan badan air Sungai Kapuas tidak mendapatkan perhatian pengelolaan sumber daya air yang baik. Secara eksisting, kondisi permukiman di tepian Sungai Kapuas sangatlah memprihatinkan. Terdapat banyak kampung yang tumbuh ditepian Sungai Kapuas. Kampung – kampung tersebut dinilai tidak layak huni karena munculnya masalah permukiman kumuh seperti ketidakteraturan bangunan, tingkat kepadatan bangunan yang tinggi, kualitas struktur bangunan gedung, sarana dan prasarana lingkungan yang tidak memenuhi syarat teknis dan tidak melayani permukiman, serta fasilitas umum dan fasilitas sosial yang tidak memadai bagi penduduknya. Salah satunya adalah Kampung Caping dan Kampung Tudong. Walaupun sudah ada upaya - upaya penataan kawasan kumuh telah direalisasikan oleh program-program pemerintah, namun secara eksisting selain citra kawasan permukiman tepian sungai Kampung Caping dan Kampung Tudong yang belum bisa memberikan keindahan dan penghijauan yang lestari pada fisik lingkungannya, kawasan permukiman juga belum berkapabilitas dalam pemenuhan kebutuhan akan sarana prasarana lingkungan untuk mendukung aktivitas masyarakat yang tinggal di dalam kampung tepian Sungai Kapuas. Maka, penelitian ini dilaksanakan dengan harapan dapat mengidentifikasi masalah kekumuhan yang terjadi di Kampung Caping dan Kampung Tudong secara eksisting. Penelitian ini akan dilakukan menggunakan metode analisis deskriptif, analisis kondisi eksisting, dan analisis standar regulasi sesuai ketentuan dari peraturan menteri dan standar nasional.